If a/b = b/c = c/d,then how do I prove that (a-d)^2 = (b-c)^2 +(c-a)^2 + (b-d)^2?

1 Answer
Oct 8, 2017

See explanation

Explanation:

We want to show that:

(a-d)^2=(b-c)^2+(c-a)^2+(b-d)^2

Expanding the expression on the right:

b^2-2bc+c^2+c^2-2ac+a^2+b^2-2bd+d^2

Rearranging and combining terms:

a^2+2b^2+2c^2-2ac-2bc-2bd+d^2

Factoring out the 2:

a^2+2(b^2+c^2-ac-bc-bd)+d^2

Now let’s use the fact that a/b=b/c

Multiply everything by bc, so:

color(red)(ac=b^2)

Same thing for b/c=c/d but multiply by cd, so:

color(blue)(bd=c^2)

Same thing for a/b=c/d but multiply by bd, so:

color(green)(ad=bc)

Find and replace these terms in our expression:

a^2+2(color(red)(b^2)+color(blue)(c^2)-ac-color(green)(bc)-bd)+d^2

a^2+2(color(red)(ac)+color(blue)(bd)-ac-color(green)(ad)-bd)+d^2

Combine like terms inside the parentheses:

a^2+2(-ad)+d^2=a^2-2ad+d^2

Factor:

(a-d)^2

Therefore:

(a-d)^2=(b-c)^2+(c-a)^2+(b-d)^2